دلالة المصدر الصرفية في النصوص القرآنية = Significance of the morphological source in the Qur’anic texts = kepentingan sumber morfologi dalam teks Al-Quran - Abdul Majid, Abu Saiid Muhammad (International Islamic University Malaysia, 2012)
The Holy Qur’an is an authority on the Arabic language as it is an authority in Islamic SharÊ‘ah. The text of the Qur’an is the authentic text and authority on Arabic language, morphology and grammar. This research aims to consolidate the morphological significance of the Qur’an through the study of its most eloquent literary style of all times, to explore the colorful manifestations of this significance in furnishing this style, and to highlight the importance of studying morphology in light of the Qur’anic style, which resolves some of the controversial issues concerning the morphological significance of the source. The research adopts inductive-descriptive and analytical methods.